Evaluation of the Central Hearing Process in Parkinson Patients - Zeigelboim, Bianca Simone; Klagenberg, Karlin Fabianne; Muñoz, Monica Barby; Gorski, Leslie Palma; Teive, Hélio A. Ghizoni; Santos, Rosane Sampaio (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Parkinson disease (PD) is a degenerating disease with a deceitful character, impairing the central nervous system and causing biological, psychological and social changes. It shows motor signs and symptoms characterized by trembling, postural instability, rigidity and bradykinesia.Objective: To evaluate the central hearing function in PD patients.Method: A descriptive, prospect and transversal study, in which 10 individuals diagnosed of PD named study group (SG) and 10 normally hearing individuals named control group (CG) were evaluated, age average of 63.8 and (SD) 5.96. Both groups went through otorhinolaryngological and ordinary audiological evaluations, and dichotic test of alternate disyllables (SSW).Results: In the quantitative analysis, CG showed 80% normality on competitive right-ear hearing (RC) and 60% on the competitive left-ear hearing (LC) in comparison with the SG that presented 70% on RC and 40% on LC. In the qualitative analysis, the biggest percentage of errors was evident in the SG in the order effect. The results showed a difficulty in identifying a sound when there is another competitive sound and in the memory ability.Conclusion: A qualitative and quantitative difference was observed in the SSW test between the evaluated groups, although statistical data does not show significant differences. The importance to evaluate the central hearing process is emphasized when contributing to the procedures to be taken at the therapeutic follow-up.
Keywords: Parkinson disease; hearing perception; hearing